Centrality of Hygienic Honey Bee Workers in Colony Social Networks - Adrian Perez; Brian R. Johnson (Insects)
Many social and environmental variables can affect the interactions among individuals in an insect colony that fundamentally structure its social organization. Along with important attributes such as age and caste, immunity-related factors such as the performance of sanitary tasks or exposure to a pathogen can also influence an individual’s social interactions and their place in the resulting social network. Most work on this subject has supported the hypothesis that health-compromised individuals will exhibit altered social or spatial behavior that presumably limits the spread of infection. Here, we test this hypothesis using honey bee workers recently involved in hygienic behavior, an important set of sanitary tasks in which unhealthy brood are uncapped and then removed from the colony. Using static social networks, we quantify the interaction patterns of workers recently involved in hygienic tasks and compare their network centrality to non-hygienic workers. Using dynamic networks, we analyze the capability of hygienic workers to spread a potential infection throughout the colony. We find no substantial differences in how connected hygienic workers are in the network, and we show that hygienic workers would spread a novel infection throughout the colony to the same extent as non-hygienic workers. Our results suggest that experience with certain sanitary tasks may not necessarily produce rapid changes in social behavior. This work highlights the importance of considering the benefits of remaining socially integrated in important information networks and the temporal limitations for how quickly organized immune responses can occur in response to potential infections.